Echocardiographic Findings Suggestive of Infective Endocarditis in Asymptomatic Danish Injection Drug Users Attending Urban Injection Facilities - Axelsson, Anna; Søholm, Helle; Dalsgaard, Morten; Helweg-Larsen, Jannik; Ihlemann, Nikolaj; Bundgaard, Henning; Køber, Lars; Iversen, Kasper (The American journal of cardiology, 2014)
Injection drug users (IDUs) account for a considerable number of the hospitalizations for infective endocarditis (IE), but the prevalence of diagnosed and unrecognized IE in IDUs is unknown. The aim of the present study was to assess the prevalence of valvular abnormalities suggestive of IE in IDUs attending a supervised injection facility. We performed transthoracic echocardiographic examinations on-site in the injection facilities. A total of 206 IDUs (mean age 43 ± 9 years, 23% women) with a median injection drug abuse of 18 years (interquartile range 10 to 26) were included. Fourteen IDUs (14 of 206, 7%, 95% confidence interval [CI] 4% to 11%) had a previous history of IE. IDUs with a history of IE were significantly older than IDUs without a history of IE (48 ± 8 vs 42 ± 9 years, respectively, p = 0.03) and had a longer duration of injection drug use (27 [18 to 36] vs 17 years [10 to 25], p = 0.008). In the subgroup of IDUs with a history of IE, 4 subjects (4 of 14, 29%, 95% CI 11% to 55%) had persistent or relapse vegetations. Of the remaining 10 IDUs with a history of IE, 5 (5 of 10, 50%, 95% CI 24% to 76%) had moderate-to-severe regurgitation. In the subgroup of IDUs without a history of IE, vegetations were seen in 9 subjects (9 of 192, 5%, 95% CI 2% to 9%). This group of IDUs with possibly unrecognized IE was older than IDUs without vegetations (48 ± 12 vs 42 ± 9, respectively, p = 0.04). Among the IDUs without a history of IE who did not have vegetations, 30 IDUs (30 of 183, 16%, 95% CI 11% to 22%) had moderate-to-severe regurgitation with or without concomitant thickening of leaflets. Thus, in IDUs without a history of IE, some extent of valvular abnormalities was seen in 20% (39 of 192, 95% CI 15% to 27%) of subjects. None of the IDUs with valvular vegetations had current symptoms consistent with active IE. In conclusion, valvular abnormalities assessed by echocardiography were prevalent in asymptomatic IDUs without a medical history of IE, and vegetations were seen in 5% of subjects.